Genetic analysis of insect bite hypersensitivity (summer eczema) in Icelandic horses - S. Eriksson (Animal, 2008)
There is a lack of knowledge about the genetic background of eczema due to insect bite hypersensitivity, also called summer eczema, in horses. The condition is known in several horse breeds and countries and it causes reduced welfare of the horse and economic losses to the owner. The aim of this study was to estimate genetic parameters for summer eczema in Swedish-born Icelandic horses. A questionnaire was sent to owners of horses sired by stallions with more than 50 offspring born in Sweden between 1991 and 2001. Variance components of summer eczema classified as healthy, mild, moderate or severe were estimated using the threshold methodology with sire models. In addition, summer eczema was analysed as a binary trait (healthy v. affected). The analyses included 1250 horses sired by 33 stallions. The prevalence of summer eczema was 8%, with a range of 0% to 30% in different paternal half-sib groups. Offspring of dams suffering from eczema had a higher risk of developing eczema. The heritability for severity of summer eczema was estimated at 0.3 (s.d. < 0.2) with a threshold sire model. In contrast to the age of the horse, different geographic areas and gender were significantly associated with severity of the eczema. We conclude that genetic selection could decrease the prevalence of summer eczema among Swedish-born Icelandic horses. The amount and quality of data are, however, crucial for the possibility to introduce a genetic evaluation of summer eczema. The symptoms should be classified in several classes according to severity, and this classification could be made by the horse owner.